PENGARUH PEMBERIAN PUPUK ORGANIK CAIR JERAMI PADI TERHADAP PERTUMBUHAN TANAMAN TOMAT (Solanumlycopersicum) - Harniwati Dakhi (Universitas Nias Raya, 2022)
Lack of understanding of farmers in Bawomaenamolo village in utilizing rice straw as liquid organic fertilizer. This study aims to determine the effect of using straw as organic fertilizer on the growth of tomato (Solanumlycopersicum) plants. This research uses quantitative research with pure experimental method (True Experiment) and Completely Randomized Design (CRD) research design. The population of this study was tomato plants which consisted of 30 plants. The sample in this study was tomato plants, which consisted of 6 treatments and 5 replications. The data in the research was analyzed using the Kolmogorov-Smirnov test for normality, homogeneity and ANOVA tests for hypothesis testing using the SPSS version 20 application. Suggestions offered by researchers, the use of organic rice straw fertilizer can be applied to reduce the use of inorganic fertilizers (chemical) so as to improve the quality of agriculture.